Simulationsstudien zur Theorie der oberen Baumgrenze - Schwarz, Reiner (ERDKUNDE, 1983)
Hitherto global upper timber-line surveys have had to do without accurate control of thermal growth conditions in any study region. In order to overcome the difficulties of estimating the maximum altitude of tree growth conformable to theory, a simulation model named SIMBA has been developed. Meeting the frost dehydration theory (= FTT) in its essence, the model proceeds from the idea that a lack of summer heat prohibits full ripening of the leaves, reducing protection against water loss if, in the following winter and spring time, water supply is blocked by frozen ground. Such events may cause lethal water deficits for the leaves. The model is driven by a stochastic temperature generator which produces mean daily temperatures and oscillations proceeding from parameters measured at a nearby reference station. The upper boundary of thermally-constrained tree growth can be evaluated by varying the corresponding height parameter. Results are tested against the observed altitude of the timber-line. Residuals as well as model behaviour give information about the range of the theory's validity. The study confirms tree growth as being limited in cold and cool temperate northern latitudes, continental boreal climates included, as postulated by FTT. An exception has to be made for the oceanic climate of the island arc of East Asia, where collapse by snow over charge is considered to be a stronger limiting factor. The model is also valid for dry-summer subtropical regions of the northern hemisphere. Under these climatic conditions, tree growth is not affected by reduced maturity of leaves, frost dehydration being their only cause of death. Extreme exposition differences in the E-W oriented ranges of the Himalayas can be considered by variation of the latitude input parameter. Having furnished evidence for the FTT referring to the holarctic flora, great residuals in climatically comparable southern hemisphere regions stand for floristic differences. Central Chile exhibits residuals caused by a lack of neotropic species comparable with northern conifers. Simulation runs for tropical high mountains show a declining tree growth before frost dehydration actually occurs. But observed timber-lines regularly lie 200 m below the modelled limits. Limiting factors of tree growth under tropical conditions have therefore to remain obscure.